2019
DOI: 10.1016/j.neuroimage.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Executive control training does not generalize, even when associated with plastic changes in domain-general prefrontal areas

Abstract: How executive function training paradigms can be effectively designed to promote a transfer of the effects of interventions to untrained tasks remains unclear. Here, we tested the hypothesis that training with a complex task involving motor, perceptual and task-set control components would result in more transfer than training with a simple motor control task, because the Complex training would lead to more involvement-and in turn modification-of domain-general executive control networks. We compared performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 85 publications
4
16
0
Order By: Relevance
“…Second, while corresponding effects of short and longterm training have been found with neutral stimuli (Chavan et al, 2015;Simonet et al, 2019), we cannot rule out that long-term training might affect differently reward responses.…”
Section: Limitationsmentioning
confidence: 78%
“…Second, while corresponding effects of short and longterm training have been found with neutral stimuli (Chavan et al, 2015;Simonet et al, 2019), we cannot rule out that long-term training might affect differently reward responses.…”
Section: Limitationsmentioning
confidence: 78%
“…Despite modulations within domain-general IC areas, the authors found no transfer effects, which suggests that different facets or subcomponents of IC rely on specific regions within this domaingeneral IC network (Dillon and Pizzagalli, 2007). While different IC tasks have been investigated to clarify the organization of this network and its subcomponents (Dillon and Pizzagalli, 2007;Spierer et al, 2013;Liu et al, 2016;Chavan et al, 2017;Rey-Mermet et al, 2018;Simonet et al, 2019), whether specific IC brain regions support different response effectors remains unknown.…”
Section: Introductionmentioning
confidence: 92%
“…Neurophysiologically, previous literature has postulated the existence of domain-general IC mechanisms that support all inhibitory tasks (Spierer et al, 2013). It has also been advanced that depending on the task's demands (Dillon and Pizzagalli, 2007;Simonet et al, 2019) or the response modality (Leung and Cai, 2007), more specific IC processes can be engaged.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations